Sukces małżeński w nowej odsłonie – interpretacje postbadawcze - Linek, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
Today, everyday life is focused on achieving success, which often dominates in the creation of individual aspirations, often with an egocentric focus on making oneself happy. Meanwhile, the creation of a long-term marriage, or even a partnership, tends to lean towards bilateral mutual references, which usually exclude focusing attention only on oneself and put a question mark in the field of interpretation of what success in a marriage relationship is, what determines it today, which makes it difficult to implement it, and finally – what strategies seem to be most effective when success does not come. These questions were asked during the research project concerning, among others, understanding success on the basis of marital and partner relationships. In order to obtain answers to the questions posed, a quantitative study was conducted on a representative sample of adult Poles (N = 1121). It was carried out by the Ariadna panel from July to August 2022 using CAWI. It was possible to outline certain trends in creating the concept of success and its determinants, as well as difficulties and strategies that are undertaken in its field, which – as it results from the analyses carried out – are still largely based on the traditional axiological approach. At the same time, they have certain clear tendencies resulting from the features of postmodernity. It is still valid – seen as a success – to build a relationship based on friendship, support and love, with an important dimension of emotional and sexual relationship. However, it is more challenging to change one’s own behaviour today. There is also a high degree of acceptance for attention focused on pursuing one’s own desires and pleasures. There were also interesting discrepancies regarding the upbringing of children as an essential dimension of success in a relationship, and numerous statistically significant differences indicating the role of socio-demographic variables (gender, age, education, marital status, having children, faith and religious practices), which differentiate the respondents in their understanding of the issues raised in the study. Thus, the image of success in marriage seems to sparkle with various shades of individually selected colours but with a clear traditional outline.